The Moderating Role of Personal Resources Between Demands and Ill-Being of Romanian Healthcare Professionals in the COVID-19 Pandemic - Secosan, Ica; Virga, Delia; Crainiceanu, Zorin Petrisor; Bratu, Lavinia Melania; Bratu, Tiberiu (Frontiers in Public Health, 2021)
Background and objectives: The illness caused by the new coronavirus (COVID-19) triggered considerable mental consequences for the medical staff. Our aim was to research whether frontline healthcare workers’ positive psychological state—PsyCap—impacts the relationship between anxiety/depression and burnout/mental health complaints. Material and methods: One hundred twenty-six medical professionals working on the frontline at the Intensive Care Unit and Emergency Department in Romania took validated surveys between March and April 2020. All information was collected online after accessing a link that was received in an email message. The inclusion criteria concerned the categories of healthcare professionals who came into direct contact with patients during the COVID-19 global epidemic through the performed medical act, as well as time spent in the medical field of ICU an EM, namely at least one year in the department. We excluded from the research other categories of employees and auxiliary staff, as well as healthcare workers with less than one-year of experience in the medical field. The moderating role of personal resources (PsyCap) between demands (such as anxiety and depression) and ill-being (burnout and mental health complaints) of healthcare professionals were tested via hierarchical multiple regressions. Results: We tested the moderating role of PsyCap on the relation between anxiety and ill-being. The results indicated that high anxiety predicts lower emotional exhaustion and a low level of mental health complaints about Romanian healthcare professionals when PsyCap is high. The moderating role of PsyCap on the relation between depression and ill-being was tested in the second hypothesis. The results indicated that high depression predicts lower inefficacy and a low level of mental health complaints about Romanian healthcare professionals when PsyCap is increased. Conclusions: PsyCap is a crucial variable that may decrease the impact of anxiety and depression on psychological outcomes such as emotional exhaustion, inefficacy, and psychological problems among Romanian medical professionals working on the frontline during the COVID-19 global epidemic. Thus, psychological interventions that help medical staff gain personal resources are appropriate in the context of the COVID-19 pandemic.